Distinct serum proteome profiles associated with collagen‐induced arthritis and complete Freund's adjuvant‐induced inflammation in CD38−/− mice: The discriminative power of protein species or proteoforms. Issue 19 (28th August 2015) - Rosal‐Vela, Antonio; García‐Rodríguez, Sonia; Postigo, Jorge; Iglesias, Marcos; Longobardo, Victoria; Lario, Antonio; Merino, Jesús; Merino, Ramón; Zubiaur, Mercedes; Sancho, Jaime
<x xml:space="preserve">Abstract</x> Collagen‐type‐II‐induced arthritis (CIA) is an autoimmune disease, which involves a complex host systemic response including inflammatory and autoimmune reactions. CIA is milder in CD38−/− than in wild‐type (WT) mice. ProteoMiner‐equalized serum samples were subjected to 2D‐DiGE and MS‐MALDI‐TOF/TOF analyses to identify proteins that changed in their relative abundances in CD38−/− versus WT mice either with arthritis (CIA+), with no arthritis (CIA−), or with inflammation (complete Freund's adjuvant (CFA)‐treated mice). Multivariate analyses revealed that a multiprotein signature (n = 28) was able to discriminate CIA+ from CIA− mice, and WT from CD38−/− mice within each condition. Likewise, a distinct multiprotein signature (n = 16) was identified which differentiated CIA+CD38−/− mice from CIA+ WT mice, and lastly, a third multiprotein signature (n = 18) indicated that CD38−/− and WT mice could be segregated in response to CFA treatment. Further analyses showed that the discriminative power to distinguish these groups was reached at protein species level and not at the protein level. Hence, the need to identify and quantify proteins at protein species level to better correlate proteome changes with disease processes. It is crucial for plasma proteomics at the low‐abundance protein species level to apply the ProteoMiner enrichment. All MS data have been deposited in the ProteomeXchange with identifiers PXD001788, PXD001799 and PXD002071 (http://proteomecentral.proteomexchange.org/dataset/PXD001788, http://proteomecentral.proteomexchange.org/dataset/PXD001799 and http://proteomecentral.proteomexchange.org/dataset/PXD002071).